(untitled) (Research, Society and Development, 2025)
Background: Peripheral odontogenic fibroma (POF) is a rare benign mesenchymal odontogenic tumor, representing only 0.05% of biopsy specimens. Despite its rarity, POF is considered the most prevalent peripheral odontogenic tumor. Conducting a systematic review is essential to determine the predominant epidemiological, clinical, and histological characteristics of POF, assisting dentists in similar cases. Aim: This study aimed to elucidate the epidemiological, clinical, and histological characteristics of POF through a systematic review. Methods: The systematic review followed the PRISMA criteria. The clinically relevant question was: What is the epidemiological, clinical, and histological profile of POF. Articles in English were included, with individuals (humans) with a histological diagnosis of POF. Literature review articles that did not define the type of lesion were excluded. The search was conducted in several databases until December 2016. Results: Of the 964 articles, only 49 were eligible. The most frequent epidemiological characteristics were white women between the 2nd and 4th decades of life. Clinically, the lesions were located mainly in the mandibular gingiva, with characteristics of a nodule, ulcerated or not, sessile, red, smooth, or lobed surface, and an average size of 1.71 cm. The main histopathological findings were the absence of ulceration of the superficial epithelium, fibrocellular connective tissue, with or without calcifications, non-encapsulated lesion, with abundant or scarce presence of islands and strands of odontogenic epithelium. Conclusion: This topic requires more articles with a higher level of scientific evidence, such as a systematic review, requiring greater scientific rigor in the quality of these articles.